1975
DOI: 10.1128/iai.12.1.193-197.1975
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal synthesis of staphylococcal exfoliative toxin

Abstract: Tox-+ staphylococcal strains, as opposed to Tox-minus strains, produce epidermal exfoliation within 18 h after direct subcutaneous or intraperitoneal injection into newborn mice. The extracellular product responsible for exfoliation is termed exfoliative toxin (ET). When culture supernatant fluid from the plasmid-cured Tox-minus substrains UT 0100 or UT 0111 or from six naturally occurring phage group 2 Tox-minus strains was concentrated 20-fold and inoculated into newborn mice, ET activity could be detected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Later it was shown that tox-substrains produced by curing naturally occurring tox+ strains could produce traces of toxin. ET was detected in these strains when their culture filtrates were concentrated 20-fold before injection into suckling mice (11). This observation suggested the possibility that a small amount of ET is coded for by chromosomal genes in these strains, or that they retained subdetectable amounts of plasmid deoxyribonucleic acid that could function in the production of small amounts of ET.…”
mentioning
confidence: 92%
“…Later it was shown that tox-substrains produced by curing naturally occurring tox+ strains could produce traces of toxin. ET was detected in these strains when their culture filtrates were concentrated 20-fold before injection into suckling mice (11). This observation suggested the possibility that a small amount of ET is coded for by chromosomal genes in these strains, or that they retained subdetectable amounts of plasmid deoxyribonucleic acid that could function in the production of small amounts of ET.…”
mentioning
confidence: 92%
“…Several studies have shown that elimination of plasmids by treating ETB-producing strains with EtBr (5,16,21), SDS (5,16,21) or heat (5,16,21) converts them to non-ETB-producers. Johnson et al (4) observed that the S. aureus strains tested had been identified earlier as ETA-and ETB-producing strains immunologically, although neither the etb gene nor ETB toxin could be demonstrated in these isolates using their tests.…”
Section: Discussionmentioning
confidence: 99%
“…These strains, when cured, manifest significant decreases in exfoliatin production, but some residual toxin production can usually be demonstrated. Keyhani et al (5) have suggested that toxin production may be under both chromosomal and extrachromosomal control. The greatest relative reduction in exfoliatin production after plasmid elimination seems to occur with parent strains that are not "good" toxin producers (M. Rogolsky, personal communication), as exemplified by UT-0003 and UT-0003-4.…”
Section: Discussionmentioning
confidence: 99%